Gambaran Umum Nelayan Gurita di Desa Kadoda Kabupaten Tojo Una-Una Provinsi Sulawesi Tengah - Nuralim Pasisingi (Journal of Tropical Diversity, 2025)
This study aimed to determine the location of fishing, fishing gear, catches, and the income and expenditure of octopus fishermen in Kadoda Village, Talatako Island, Togean Islands, Tojo Una-Una Regency, Central Sulawesi Province. The method used was an interview. The respondents in this study were 20 octopus fishermen. Secondary data on octopus catches were obtained from the natural resource advocacy network (JAPESDA) of Gorontalo Province. The research data were visualized in the form of tables or graphs and interpreted descriptively. The results of the study showed that the octopus fishing locations in Kadoda Village included Ref Popolii, Dambulalo, Ref Karang, Tasi Malino, Binuang, Kadoda Waters, Batu Engkang, Angkaio, and Tongkabo. The fishing gear used by fishermen was 90% using gara gara ketang and 10% using spears. The average catch of octopus fishermen when the weather was good was 5-8 per trip per fisherman. However, the average catch was only around 1-2 per trip per fisherman if the weather was bad. The income per fisherman from selling octopus ranges from Rp. 300,000 to Rp. 500,000 per trip, while the expenditure was Rp. 150,000 to Rp. 300,000 per trip per fisherman.